A protocol to analyze the global literature on the clinical benefit of interlimb-coordinated intervention in gait recovery and the associated neurophysiological changes in patients with stroke - Li, Shijue; Zhang, Haojie; Leng, Yan; Lei, Di; Yu, Qiuhua; Li, Kai; Ding, Minghui; Lo, Wai Leung Ambrose (Frontiers in Neurology, 2022)
Background Stroke is among the leading causes of disability of worldwide. Gait dysfunction is common in stroke survivors, and substantial advance is yet to be made in stroke rehabilitation practice to improve the clinical outcome of gait recovery. The role of the upper limb in gait recovery has been emphasized in the literature. Recent studies proposed that four limbs coordinated interventions, coined the term “interlimb-coordinated interventions,” could promote gait function by increasing the neural coupling between the arms and legs. A high-quality review is essential to examine the clinical improvement and neurophysiological changes following interlimb-coordinated interventions in patients with stroke. Methods Systematic review and meta-analysis will be conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature will be retrieved from the databases of OVID, MEDLINE, PubMed, Web of Science, EMBASE, and PsycINFO. Studies published in English over the past 15 years will be included. All of the clinical studies (e.g., randomized, pseudorandomized and non-randomized controlled trials, uncontrolled trials, and case series) that employed interlimb intervention and assessed gait function of patients with stroke will be included. Clinical functions of gait, balance, lower limb functions, and neurophysiologic changes are the outcome measures of interest. Statistical analyses will be performed using the Comprehensive Meta-Analysis version 3. Discussion The findings of this study will provide insight into the clinical benefits and the neurophysiological adaptations of the nervous system induced by interlimb-coordinated intervention in patients with stroke. This would guide clinical decision-making and the future development of targeted neurorehabilitation protocol in stroke rehabilitation to improve gait and motor function in patients with stroke. Increasing neuroplasticity through four-limb intervention might complement therapeutic rehabilitation strategies in this patient group. The findings could also be insightful for other cerebral diseases.